Mycological Analysis of the Oral Cavity of Patients Using Acrylic Removable Dentures - Bartłomiej W. Loster; Jolanta Loster; Aneta Wieczorek; Wojciech Ryniewicz (Gastroenterology Research and Practice)
Background. The problems of fungal infections in edentulous have been discussed in literature. Findings show that oral mycosis has an influence on the mycosis of oesophageal mucosa. Based on this we started to follow from 2007 in patients who wear dentures mycological examination, to evaluate changes of yeasts numbers, the sensitivity to antibiotics and determine the impact of types of prosthesis, time of using, gender and age of patients. 1230 patients who were wearing dentures participated in the retrospective study. The material for mycological examination was sampled as a smear from the palate. After the mycological identification of Candida species and assessment of growth, the susceptibility testing with Fluconazole and Nystatin was made. The number of 23 Candida species was diagnosed microbiologically in five years. C. albicans and C. glabrata were increasing in number—from 33,7% to 46,9% and 6,7% to 14,0%, respectively. There was a significant statistical difference between yeasts growth and gender (P=0,017<0.05). The conclusion is that a large percentage of persons wearing removable denture has been affected by Candida species and that could lead to the mycosis of farther gastrointestinal tract sections. The mycological examination before treatment, especially in patients using acrylic denture, appears to be necessary.